Perceived risk of developing cancer in a suburban community in Malaysia - Pasi, Hafizah; Md Isa, Zaleha; Shah, Shamsul Azhar (Asian Pacific Organization for Cancer Prevention (APOCP), 2018)
Objective: To determine the perceived risk of developing cancer in a suburban community in Malaysia. Methods: A cross sectional study using a simple random sampling was conducted among residents aged 18 years old and above (n=520) who had never been diagnosed with cancer, in selected households in a suburban area of Pahang state in Malaysia. The study instruments were a validated questionnaire on risk perception, an automatic blood pressure monitor,a weighing scale and a measuring tape. Data were analyzed using IBM SPSS Statistics for Windows, Version 20.0 and the p value was taken at p <0.05 as significant. Result: This study revealed that only 5.0 percent individuals perceived they were at risk cancer, whilst the perceived severity was 41.3 percent. Multi variable analysis showed a significant association only for a family history of cancer (adjusted OR of 4.80; 95% CI = 1.45-15.82) (p=0.010) among thispopulation. Conclusion: The perceived risk of developing cancer in the selected suburban community of Pahang state in Malaysia is low as compared to that for other non-communicable diseases in this country, whilst the perceived severity was higher than for other diseases. Thus, considering the importance of correct perceptions for behavioral changes,more health education and promotion is needed to make the community better aware of the actual threat of cancer.